SURVEI PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS DIGITAL PADA MAHASISWA BARU POR UMS SEMESTER GASAL T.A 2020/2021 - Gatot Jariono; Nur Subekti; Nurhidayat; Eko Sudarmanto (Bajang Institute, 2021)
This survey revealed the use of digital-based learning media for new UMS Sports Education students in the odd semester T.A of 2020/2021. The purpose of this study was to explore perceptions, strategies, and challenges for new students, especially in the learning process during the transition period of the covid 19 pandemics. The experience of learning from home became a new habit in the learning process from an early age, elementary level, middle level to the university that occurred. since the onset of the Covid-19 pandemic which is impossible to repeat. The population and sample of this study were all new UMS Sports Education students who filled out a questionnaire totaling 70 people. The technique of data analysis used data reduction, data presentation, and conclusion drawing. Descriptive frequency analysis was used in analyzing research data. The results of the survey show that (i) the learning media used in schools during the pandemic are WhatsApps; (ii) Information obtained about the sports education study program is from family/friends; (iii) The method used by new students to inform the sports education study program in the social environment is through social media; (iv) The sport that the sports education program wants to develop is football; and (v) Non-sports achievements that want to be developed in the Sports Education study program are student organizations.